Effect of larval stocking density on growth, survival and whole body cortisol of the Mediterranean mussel Mytilus galloprovincialis (Lamarck, 1819) larvae reared under laboratory conditions. (13th November 2013) - Lagos, Luis; Herrera, Marcelino; Sánchez‐Lazo, Clara; Martínez‐Pita, Inés
Abstract Interest of mussel hatchery development has increased during the last years as natural seed collection does not always satisfy the demand of producers. Success on larval bivalve culture depends on several factors such as diet, temperature or stocking density. In this study, the effect of larval density in mussel culture success has been assessed testing three larval densities: high (50 larvae mL−1), medium (25 larvae mL−1) and low (5 larvae mL−1). Results showed higher growth and survival at low density but the amount of postlarvae was low. The highest number of settled larvae was observed at high density but mortality was also high and a delay on the larval development was detected producing a prolongation on the culture length. However, medium density resulted in a good survival and growth and also in a considerable amount of postlarvae, as this density could be adequate for massive mussel seed production. Cortisol content on the larvae and postlarvae was also analysed and significant differences were obtained among groups probably due to the stress associated to settlement and metamorphosis.